2021
DOI: 10.1001/jamanetworkopen.2020.33004
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Food and Drug Administration– and European Medicines Agency–Approved Systemic Oncology Therapies and Clinically Meaningful Improvements in Quality of Life

Abstract: IMPORTANCE For patients with cancer treated with palliative intent, quality of life (QOL) is a critical aspect of treatment decision-making, alongside survival. However, regulatory approval can be based solely on survival measures or antitumor activities, without QOL evidence. OBJECTIVE To investigate whether recently approved oncology therapies demonstrate clinically meaningful improvements in QOL. EVIDENCE REVIEW This systematic review study identified oncology drug indications approved by the US Food and Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…Also, J o u r n a l P r e -p r o o f concurrent care may enhance patients with cancer' quality of life, an issue frequently overlooked even under the protected umbrella of a clinical trial. [31] Third, unlike other trials investigating the effect of specific nutritional formulas, [32] we used a variety of nutritional support strategies with the support of trained dieticians to reach nutritional goals. Our trial does thus not provide evidence for effects of single nutritional components, but rather suggests that the overall strategy of providing nutritional support to reach different nutritional goals during a hospital stay for an acute illness is beneficial for patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Also, J o u r n a l P r e -p r o o f concurrent care may enhance patients with cancer' quality of life, an issue frequently overlooked even under the protected umbrella of a clinical trial. [31] Third, unlike other trials investigating the effect of specific nutritional formulas, [32] we used a variety of nutritional support strategies with the support of trained dieticians to reach nutritional goals. Our trial does thus not provide evidence for effects of single nutritional components, but rather suggests that the overall strategy of providing nutritional support to reach different nutritional goals during a hospital stay for an acute illness is beneficial for patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 2020 2012–2017 106 trials led to FDA approvals of 52 drugs for 96 indications: thresholds of clinical benefit were met in 43% of ASCO-VF, 34% of ESMO-MCB, 73% of ASCO-CRC (OS >2.5 months and PFS > 3 months) and 69% of NCCN Evidence Blocks (score 4 and 5 and combined 16 or higher for efficacy, safety, quality and consistency of evidence, affordability) [ 35 ] 2021 2011–2020 pCODR-approved drugs: 78/104 submissions received positive recommendation; 61% of accepted submissions considered of benefit based on ESMO-MCBS as to 19.2% in rejected submissions [ 18 ] 2021 2006–2019 FDA approved 55 oncology drug indications scorable with ASCO-VF with subsequent publications relevant for reassessing ASCO-VF scoring: at FDA approval 40.0% substantial benefit (score ≥45), 49.1% low (score ≤40) and 10.9% intermediate. At 3 years post approval based on 9 follow-up publications, despite changes in individual scores, 40.0% remained substantial, 50.9% low (score ≤40) and 9.1% intermediate [ 37 ] 2021 2006–2017 214 FDA and 170 EMA approvals with 40 and 58% of indications including QOL assessment in trials; using ASCO-VF and ESMO-MCB scales, QOL bonus criteria were detected in 13 and 17% of FDA and 21 and 24% of EMA approvals [ 36 ] Quality of life: studies show PROs are often not studied and that adherence to CONSORT-PRO guidelines in oncology drug research is not optimal YOP Timespan study Results 2015 2007–2011 325 phase 3 RCTs reviewed only 48% of trials reporting PROs. PRO reporting with mean PRO RQS 5 on an 11-point scale [ 22 ] 2015 2004–2013 RCTs including PRO endpoint identified in 557 RCTs; <50% reported at least 4/6 CONSORT-PRO items [ 25 ] 2016 2003–2013 62 new drugs approved by FDA and EMA: 17 (32%) demonstrated improvement in QOL based on empirical evidence [ 17 ] 2017 2009–2013 EMA approved 48 cancer drugs for 68 indications: 9/68 (13.2%) associated with an increase in QOL [ 14 ] 2019 2014–2017 Of 160 published RCTs based on NIHR registered protocols with PROs included in endpoints, 61 (38.1%) did not include PROs in any publication.…”
Section: Critical Interpretation Of Clinical Trialsmentioning
confidence: 99%
“…A study examining the use of QoL data in regulatory approvals found that few indications met defined criteria for clinically meaningful improvement in QoL [30]. One of the reasons may be the lack of standardization in these measures, which makes comparisons across trials difficult and may cause regulatory authorities to place less emphasis on their applicability to the approvals process [30,31]. Lack of standardization may also result in data being at more risk of ambiguity.…”
Section: Patient Engagement In Melanoma Researchmentioning
confidence: 99%